Evaluasi Berbasis Kriteria untuk Kualitas Sistem One Click Service-Computer Based Test (OCS-CBT) pada SMK PGRI 3 Malang menggunakan Kriteria SERVQUAL Model Termodifikasi - Siti Fauziah Nurul Khotimah; Admaja Dwi Herlambang; Aditya Rachmadi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
One Click Service-Computer Based Test (OCS-CBT) is a website-based online examination system that is applied at SMK PGRI 3 Malang. The purpose of this study was to determine the quality of the One Click Service-Computer Based Test (OCS-CBT) system at SMK PGRI 3 Malang using the modified SERVQUAL model. This model consists of seven variables, namely assurance, empathy, responsiveness, reliability, website content, service quality, and satisfaction. The population of this study were active students of SMK PGRI 3 Malang in class X and XII for 1664 people. The sample was determined using the Slovin formula with a margin of error 9% and getting respondents numbered 160 people. Data obtained from the distribution of questionnaires with the technique of proportional stratified purposive sampling based on expertise. The analysis used is descriptive statistics. The results of the study showed that assurance variables (71,60%), empathy (67,00%), responsiveness (68,80%), reliability (74,80%), website content (74,20%), service quality (75,20%), and satisfaction (74,60%) is in the high category. The recommendations of this study are training employees who handle OCS-CBT, creating Service Level Agreement (SLA), implementing self help, forming service desks, adding features according to student needs, increasing internet speed, minimizing image file size or graphs, double check or preview the questions before the students work, and make a format or rules for file types and the size of content about exam questions.